POTENSI DAN PROBABILITAS KELONGSORAN LERENG TAMBANG KUARI BATUGAMPING DI DAERAH MORAMO UTARA, SULAWESI TENGGARA - Masri, Masri; Mili, Marwan Zam; Nafiu, Waode Rizky Awaliah; Wahab, Wahab; Agriawan, Husran; Ngkoimani, La Ode (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2024)
Demolition of limestone fragments in quarries can cause slope stability issues. This study aims to identify the potential for rock failures and determine the probability of failures on three quarry slopes. The type of rock failures was identified using kinematics analysis. Determining the probability of failures is also required to accommodate the uncertainty of input parameters in the factor of safety calculation. The probability of failure was determined using the limit equilibrium method and chi-square tests to fit shear strength curves on the discontinuities. The Barton-Bandis criterion was used to determine the shear strength of the discontinuities. On the slopes, the discontinuity types are bedding, joint, and shear fractures. Kinematics analysis of slope-1 and slope-2 revealed the possibility of wedge failures with an occurrence probability ranging from 19.80 to 20.81%. On slope 3, a planar failure possibility with a 69.49% of occurrence probability was identified. Even though the kinematics analysis suggested the possibility of rock failures, the factor of safety on all three slopes was above the threshold (7.28 – 30.58) with probability of failure ranging from 0 – 6.14%. Based on sensitivity analysis, factor of safety is most influenced by changes in the bedding cohesion. Variations in groundwater recharge at discontinuities also influence the factor of safety and the probability of failures, particularly in planar failures. It is recommended to evaluate other types of rock failures, such as the potential of rockfalls.